A new digital material sharing method of multimedia network teaching based on 5G communication technology. (8th September 2022) - Lai, Degang; Wang, Ke
To solve the problem of low efficiency of traditional network teaching material sharing, a new method of multimedia network teaching digital material sharing based on 5G communication technology is proposed. eXtensible Markup Language (XML) technology is used to design the digital material development model of multimedia network teaching. In order to realise the development of digital materials for multimedia network teaching, the material is packaged in modules. Based on 5G communication technology, a multimedia network teaching digital material sharing platform is developed to construct the shared service protocol and realise the efficient sharing of materials. The experimental results show that the proposed method has higher file transfer rate than the traditional method, better practical performance and better application prospect.